The information and communication technology infrastructure towards job performance among employees at Schlumberger Business Support Hub Sdn. Bhd. Bandar Utama, Petaling Jaya, Selangor / Fadhilah Makhtar - Makhtar, Fadhilah (2014)
This research was conducted to identify the relationship between ICT infrastructure and job performance among employee at Schlumberger Business Support Hub And. Bhd. This research conducted to determine the availability of ICT in the workplace, the use of the provided ICT infrastructure, the activities that have been done by using the ICT infrastructure in the workplace, and the job that has been performed by the employee by using the ICT infrastructure provided in the workplace. This study was tested to employees in Schlumberger Business Support Hub Sdn. Bhd. using the simple random sampling technique. The questionnaire was distributed to all respondents by hand in the workplace and all the result analyzed using Social Science Software (SPSS) version 22. The finding of this research is positive which is there is significant relationship between the ICT infrastructure towards job performance among employee in Schlumberger Business Support Hub Sdn. Bhd. The researcher concludes that this research ended up successfully with some of suggestion recommended from the side of employees and employers itself. Below also have the details of suggestion for future research such as broaden the size of respondents and increase the variety of the instrument.